(untitled) (Iraqi Journal of Civil Engineering, 2018)
The problem of solid waste is being emerged increasingly due to the increased quantity of solid waste as a result of population’s increase .From the point of view of environmental and energy concerns, it is preferable to reuse the organic and inorganic components of solid waste in order to minimize the cost. In this investigation, the possibility of using solid waste ash (SWA) as a partial replacement of cement and its effect on the mechanical properties of concrete was studied. Samples of municipal solid wastes were collected were burring and changed to ash. A total of 50 cubes, 15 small cubes, and 30 cylinders, as well as 5 prisms were prepared .Various properties of solid waste ash are added to the cement mistures with percent’s of 5, 10, 15 and 20 percent by weight of solid waste ash. A concrete mix with a percent solid waste ash was used as reference. Pozzolanic activities of all mortars, and setting times of all pastes, and workability of all mixes were investigated .Compressive strength, splitting tensile strength, absorption, and drying shrinkage for reference for reference and solid waste concrete specimens were investigated at various ages. Results demonstrate that the pozzolanic activity was within ASTM requirements for the cases of 5% and 10% ash replacement. For 15 and 20 percent replacement this activity was only slightly less than the ASTM value. The 90-day compressive strength rose, in comparison with control specimens, with 5 percent replacement and was only slightly lower at 10 percent replacement. In splitting tensile strength was at least equal to reference specimens for all replacement ratios. The rise in these values, over the reference specimens, ranged between 0 to 21 percent for the case of 20 and 5 percent replacement, respectively.